Fabricanon of as-spun SPEEK as a function of degree of sulfonation - Junoh, Hazlina (2015)
The purpose of this study was 10 determine the effect of degree of sulfonation (DS) on electrospun sulfonated poly (ether ether ketone) (SPEEK) fiber. SPEEK was prepared via sulfonation process by sulfonating native poly (ether ether ketone) (PEEK) with concentrated sulfuric acid (95-97%). The prepared SPEEKs polymer was characterized for their OS via hydrogen-nuclear magnetic resonance (WNMR) spectroscopy. The electrospinning process was taking placed in developing an eleetrospun SPEEK nanofibers mat and scanning electron microscopy (SEM) was used .to observe the morphological structural of the electrospun SPEEK nanofibers. SPEEK with different DS at50%, 58%, 68% and 80% was prepared in this /study.Ir was observed that the diameter of the fiber decreased as the DS increased aithe same operating parameters (flow rate and distance from needle tip to the collector), From SEM analysis, it was found that the diameter of the SPEEK nanofiber with the DS of 50('/0, 58%, 68% and 80% was 20him, 103.8nm, 68.9nin aDd 68nrn, respectively. Eventhough the obtained as-spun nanofiber from SPEEK at DS of 500/0 showed better appearance in its nanofiber mat form but the nanofiber spun at higher DS exhibited favorable lfiber 'structure due to its smaller size in diameter.In conclusion, the higher the DS of the SPEEK the smaller the diameter of the obtained fibers was.